Effects of tryptamine on duckweed growth - Qiqi Di; Wenqian Han; Yujie Han; Sizheng Liu; Yi Hu; Ziyang Qu; Yumeng Jiang; Weibo Sun; Ting Qiu; Lin Yang (Frontiers in Plant Science)
IntroductionPlant growth regulation involves complex biochemical and signaling pathways. Tryptamine (Try), a polyamine derived from tryptophan, has been implicated in plant growth and stress responses, yet its specific regulatory mechanisms have not been fully understood.MethodsThis study investigates the physiological and molecular effects of Try on Lemna turionifera 5511, focusing on its role in growth regulation, photosynthesis, and hormonal balance. Our findings reveal that Try content increases in overgrown duckweed, suggesting its involvement in aging and stress responses. Exogenous Try application at concentrations ranging from 50 to 200 μM resulted in dose-dependent growth inhibition, with 150 μM Try significantly reducing growth rate, leaf area, and chlorophyll content.ResultsThe Chlorophyll a (Chla) and Chlorophyll b (Chlb) levels were decreased by 37.5% and 40.43%, respectively. Try treatment also negatively impacted photosynthesis, as evidenced by reduced chlorophyll fluorescence parameters and downregulation of 16 photosynthesis-related genes. Additionally, Try induced oxidative stress, increasing reactive oxygen species (ROS) and peroxidase (POD) activity by 9.17% and 10.11%, respectively. While modulating endogenous hormone levels, particularly increasing abscisic acid (ABA) and decreasing cytokinin (CTK) content by 23.58% and 17.55%. Moreover, transcriptomic analysis revealed an upregulation of auxin (IAA) metabolism-related enzymes by Try addition. Meanwhile, changes in the expression of genes related to the tryptophan metabolism pathways indicate a metabolic change associated with aging.DiscussionThese results highlight the complex role of Try in regulating duckweed growth and stress responses, suggesting its potential as a regulatory molecule in plant development. Further research is needed to elucidate the molecular mechanisms underlying the influence of Try and its applications in agriculture and environmental management.